Thromboplastic Activity of Split Products of Phosphatidyl Ethanolamine - Slotta, Karl H.; Deutsch, Erwin (Thrombosis and Haemostasis, 1960)
Pure synthetic L-α-(dioleoyl) PE is inactive as a platelet substitute in the thromboplastin generation test, even when in a stable suspension. Under humid conditions it is partly hydrolyzed. Among the split products lyso PE and phosphoryl ethanolamine were identified. The resulting mixture has thromboplastin generating activity. This thromboplastin is formed slowly, but it is stable over longer periods of time than thromboplastins formed from PS + PC or PS + PE mixtures, which are rapidly generated and lose activity faster.